A method for fractional Volterra integro-differential equations by Laguerre polynomials - Dilek Varol Bayram; Ayşegül Daşcıoğlu (Advances in Difference Equations, 2018)
Abstract The main purpose of this study is to present an approximation method based on the Laguerre polynomials for fractional linear Volterra integro-differential equations. This method transforms the integro-differential equation to a system of linear algebraic equations by using the collocation points. In addition, the matrix relation for Caputo fractional derivatives of Laguerre polynomials is also obtained. Besides, some examples are presented to illustrate the accuracy of the method and the results are discussed.